Cadmium, lead and zinc leaching from smelter fly ash in simple organic acids--simulators of rhizospheric soil solutions - Ettler, Vojtech; Vrtisková, Růzena; Mihaljevic, Martin; Sebek, Ondrej; Grygar, Tomás; Drahota, Petr (Journal of hazardous materials, 2009)
Emissions from base-metal smelters are responsible for high contamination of the surrounding soils. Fly ash from a secondary Pb smelter was submitted to a batch leaching procedure (0.5-168 h) in 500 microM solutions of acetic, citric, or oxalic acids to simulate the release of toxic metals (Cd, Pb, Zn) in rhizosphere-like environments. Organic acids increased dissolution of fly ash by a factor of 1.3. Cadmium and Pb formed mobile chloro- and sulphate-complexes, whereas Zn partly present in a citrate (Zn-citrate(-)) complex is expected to be less mobile due to sorption onto the positively charged surfaces of hydrous ferric oxides (HFO) and organic matter (OM) in acidic soil.
Keywords: termodynamika; pevné částice; Oxalates; Metals, Heavy; Zinc; Citrates; Metallurgy; popel uhelný; uhlík; Solutions; koncentrace vodíkových iontů; olovo; X-Ray Diffraction; Acetates; roztoky; Lead; těžké kovy; Carbon; Cadmium; Thermodynamics; Hydrogen-Ion Concentration; Soil; acetáty; hutnictví; Particulate Matter; kadmium; oxaláty; citráty; zinek; kyseliny; Acids; půda; difrakce rentgenového záření; Coal Ash